ChemInform Abstract: Enantioselective Synthesis of Spirocyclohexadienones by NHC‐Catalyzed Formal [3 + 3] Annulation Reaction of Enals. Issue 20 (April 2016) - Yetra, Santhivardhana Reddy; Mondal, Santigopal; Mukherjee, Subrata; Gonnade, Rajesh G.; Biju, Akkattu T.
Abstract: A wide range of pyrazolone‐fused spirocyclohexadienones are obtained by reaction of α‐, β‐unsaturated aldehydes with α‐arylidene pyrazolinones involving a vinylogous Michael addition/spiroannulation/dehydrogenation cascade.